2006
DOI: 10.1186/1742-6413-3-27
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic telecytopathology of on site rapid cytology diagnoses for pancreatic carcinoma

Abstract: BackgroundDiagnosis of pancreatic lesions can be accurately performed by endoscopic ultrasound guided fine needle aspiration (EUS-FNA) with onsite cytopathologists to assess specimen adequacy and to determine a preliminary diagnosis. Considerable time is needed to perform on-site assessments. This takes away work time of cytopathologists and prohibits them from serving remote locations. It is therefore logical to ask if real-time telecytopathology could be used to assess specimen adequacy and if telecytopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 26 publications
2
46
0
Order By: Relevance
“…They did not evaluate procedure time. Kim et al [7] focused on pancreatic carcinoma and described an average total of 12 min required for telecytology, of which an average of 7.5 min were actually devoted to diagnosis because of the approximately 2 min required for whole slide scanning. They retrospectively identified 40 pancreatic cases and used only a select number of slides to review per case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They did not evaluate procedure time. Kim et al [7] focused on pancreatic carcinoma and described an average total of 12 min required for telecytology, of which an average of 7.5 min were actually devoted to diagnosis because of the approximately 2 min required for whole slide scanning. They retrospectively identified 40 pancreatic cases and used only a select number of slides to review per case.…”
Section: Discussionmentioning
confidence: 99%
“…A few recent studies have shown comparable accuracy and adequacy for telecytology when compared to conventional on-site evaluation [5,6,7,8]. One of our department’s quality incentives for 2010 was to improve cytopathologist efficiency by reducing cytopathologist procedure time by at least 50%.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we show that, in our setting, TeleCyP can provide a very rapid assessment both with EBUS (average 53.2 s) in the training phase and with EUS in the validation (average 49.2 s) phase of the study. A prior study also utilized a retrospective assessment to determine the time needed by dynamic telecytology as a modality for providing RFI for specimen adequacy [23]. Authors analyzed 40 EUS-FNA samples of the pancreas on preselected retrospective slides.…”
Section: Discussionmentioning
confidence: 99%
“…[1011121314151617181920232425] Dynamic systems appear to be more accurate compared with static systems. [678]…”
Section: Discussionmentioning
confidence: 99%